Low-Cost/High-Precision Smart Power Supply for Data Loggers - Amorim, Marcio L. M.; Ginja, Gabriel Augusto; Carmo, João Paulo; Moreira, Melkzedekue Moraes Alcântara; Siqueira, Adriano Almeida Goncalves; Afonso, Jose A. (Energies (Basel), 2023)
This paper presents a low-cost/high-precision smart power supply for application on data loggers. The microprocessor unit is the brain of the system and manages the events and was optimized to provide electrical energy to the electronic devices under normal operation and under the presence of disruptive events. The measurements showed that when switching either from battery to AC or from AC to battery, neither caused the shutdown of the power supply nor affected the behavior of the power supply. The power supply was able to charge 80% of the battery on a fast recharge of 1 h and the remaining 20% on a slow recharge of 2 h. The current allocated to the battery did not affect the operation of the power supply. The tests also showed that the power supply was able to transmit relevant information about its operation to external computers through a serial connection. This information includes the voltages at the battery and at the output of the voltage regulators, the voltage level of the AC network, the level of the battery charge and if it was being recharged, the current being drained, the internal temperatures at two locations (one measured on the resistor that limits battery charge and another measured on the output diode of the regulators), and whether the cooling system is being used. The total cost of this smart power supply is less than $150, demonstrating good potential for its popularization.